A new inorganic-organic hybrid material as consolidation material for Jinsha archaeological site of Chengdu - Wan, Tao; Lin, Jin-hui (Journal of Central South University, 2014)
An organic-inorganic epoxy-silica-acrylate (ESA) hybrid material was used for the consolidation of Jinsha archaeological site of Chengdu in China. The hybrid materials have multiple functional groups, such as anhydride, epoxy, hydroxyl and carboxyl, which can form networks at room temperature and result in an enhanced chemical and water resistance of the consolidated soil. With increasing of TEOS content, the hybrid materials keep colorless with only some reduction of transparency, while the hybrid materials obviously turn from moderate yellowish to brown yellow with the increase of the epoxy resin (EOR) content after 120 min UV irradiation. SEM observation indicates that the hybrid soil consolidation materials can effectively penetrate into the soil substrate, fill up most of the pores, decrease the area porosity and consolidate the Jinsha archaeological soil. The consolidation performances are in the sequence: ESA > K 2 SiO 4 (PS) > tetraethyl orthosilicate (TEOS).